2009
DOI: 10.1038/ismej.2009.112
|View full text |Cite|
|
Sign up to set email alerts
|

Interactions between gut microbiota, host genetics and diet relevant to development of metabolic syndromes in mice

Abstract: Both genetic variations and diet-disrupted gut microbiota can predispose animals to metabolic syndromes (MS). This study assessed the relative contributions of host genetics and diet in shaping the gut microbiota and modulating MS-relevant phenotypes in mice. Together with its wild-type (Wt) counterpart, the Apoa-I knockout mouse, which has impaired glucose tolerance (IGT) and increased body fat, was fed a high-fat diet (HFD) or normal chow (NC) diet for 25 weeks. DNA fingerprinting and bar-coded pyrosequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
628
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 885 publications
(664 citation statements)
references
References 43 publications
25
628
3
8
Order By: Relevance
“…Several studies have revealed that host-microbe interaction is an important association for developmental and homeostasis maintenance of animal traits (Nicholson et al, 2005;Zhang et al, 2010). Various reports in mouse and zebrafish revealed that the microbiota played a major role in cell proliferation (Uribe et al, 1997;Rawls et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that host-microbe interaction is an important association for developmental and homeostasis maintenance of animal traits (Nicholson et al, 2005;Zhang et al, 2010). Various reports in mouse and zebrafish revealed that the microbiota played a major role in cell proliferation (Uribe et al, 1997;Rawls et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Various reports in mouse and zebrafish revealed that the microbiota played a major role in cell proliferation (Uribe et al, 1997;Rawls et al, 2004). Based on the function, the human body has a unique symbiotic microbial niche (Hooper et al, 2002;Nicholson et al, 2005;Zhang et al, 2010;Aagaard et al, 2014). Some of the beneficial microbes of the animal gut biota can also supply vitamin B12 and riboflavin to the host (Hill, 1997;LeBlanc et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The V4 region of the 16S ribosomal RNA (rRNA) gene from DNA samples was amplified using the bacterial forward primer 5'-AYTGGGYDTAAAGNG-3' and the reverse primer 5'-TACNVGGGTATCTAATCC-3'. PCR amplification, pyrosequencing of the PCR amplicons, and quality control of raw data were performed, as described previously (Zhang et al, 2010).…”
Section: Dna Extraction and 16s-rrna-sequencing-based Studies Of Thementioning
confidence: 99%
“…48 Interestingly, in mice, genetics was shown to play less of a role than diet on the gut microbial community. 49 Age and health are also associated with alterations to the intestinal microbiota that might explain interindividual differences as well. 50 In general, dietary effects on the intestinal microbiota can occur on short and long time frames.…”
Section: ■ Living With the Past: Evolutionary History Of Diet And Thementioning
confidence: 99%